2004
DOI: 10.1562/2004-05-28-rn-181
|View full text |Cite
|
Sign up to set email alerts
|

The Separation of Hypericin's Enantiomers and Their Photophysics in Chiral Environments

Abstract: We report the first separation of the enantiomers of hypericin. Their steady-state optical spectra and ultrafast primary photoprocesses are investigated in chiral environments. Within experimental error, there is no difference between the two enantiomers in any of the systems considered. This is consistent with the emerging picture that the rich and extended absorption spectrum of hypericin is not a result of ground-state heterogeneity. It is also consistent with the observation that the spectra and photophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Derivatives of hypericin containing one or two chiral substituents in the bay position of the molecule were found to easily interconvert between the two propeller conformers at temperatures above ∼30°C, the activation energy barrier for the interconversion being in the range 70–89 kJ/mol for the various derivatives (13,14). By contrast, recent results by Sanders et al (15) have shown that the two enantiomers of hypericin could be separated and stably used for time‐resolved spectroscopy experiments. Furthermore, gymnochromes containing chiral alkyl groups as substituents in the bay position could be isomerized only by heating in pyridine at 160°C, i.e.…”
Section: Resultsmentioning
confidence: 85%
“…Derivatives of hypericin containing one or two chiral substituents in the bay position of the molecule were found to easily interconvert between the two propeller conformers at temperatures above ∼30°C, the activation energy barrier for the interconversion being in the range 70–89 kJ/mol for the various derivatives (13,14). By contrast, recent results by Sanders et al (15) have shown that the two enantiomers of hypericin could be separated and stably used for time‐resolved spectroscopy experiments. Furthermore, gymnochromes containing chiral alkyl groups as substituents in the bay position could be isomerized only by heating in pyridine at 160°C, i.e.…”
Section: Resultsmentioning
confidence: 85%
“…Hypericin, a natural compound identified in the plants of genus Hypericum (13), has been largely investigated as a photodynamic dye in the treatment of viral, bacterial infections and tumors (14–16). Binding of the photosensitizer to a biological substrate is important as it cannot only increase the residence time of the sensitizer but it may also change its photophysics ([17] and references therein). The photosensitizing effect of hypericin was described as singlet oxygen production when it is in organic solvent (18) or when it is bound to liposomic media (19) whereas when aggregated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2), they do share the common feature of extended absorption from the visible to the UV. There is growing evidence from NMR (77,78), calculations (79), and spectroscopic studies of the separated hypericin enantiomers (80) that the complexity of the hypericin absorption spectrum does not arise from inhomogeneity of the ground state. The calculations performed here for the dihydroxy and the dimethoxy perylene quinone spectra can be explained in terms of transitions to a manifold of excited singlet states.…”
Section: Discussionmentioning
confidence: 99%